Ethanol Sclerotherapy versus Laparoscopic Surgery in Management of Ovarian Endometrioma; a Randomized Clinical Trial - Hatav Ghasemi Tehrani; Raheleh Tavakoli; Maryam Hashemi; Somayeh Haghighat (Archives of Academic Emergency Medicine, 2022)
Introduction: A variety of therapeutic modalities are available in management of ovarian endometrioma. This study aimed to compare the effects of ethanol sclerotherapy and laparoscopic surgery on disease recurrence and ovarian factors of these patients.